The Prebiotic Index of Dried-Growol Made with Different Cassava Varieties and Cooking Methods - Chatarina Wariyah; Nurul Huda; Agus Slamet (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Cassava is a staple food source of carbohydrates that contain high starch levels. However, low amylose starch consumption can result in increased postprandial blood sugar. Therefore, it is necessary to provide food based on cassava, such as dried-growol, which gives a feeling of satiety for a long time and has a prebiotic effect. This research aimed to evaluate the effects of cassava varieties and cooking methods on the resistant starch (RS) content and the prebiotic index of dried-growol produced. This research was carried out in a completely randomized factorial design with two factors, namely cassava variety (M = Mentega, L = Lanting, and K = Ketan) and dried-growol cooking method (Au = Autoclave, ST = Steaming, and PC = Pressure cooker). Dried-growol was processed through preparation, fermentation, boiling, cooling, and drying. The cassava and dried-growol were analyzed for their moisture, starch, amylose, and RS content, while the prebiotic index was analyzed on dried-growol. Prebiotic index testing used two cultures of lactic acid bacteria: Lactobacillus rhamnosus and Lactobacillus plantarum. The results showed that RS levels were only influenced by cassava varieties. Dried-growols from the Lanting variety, cooked with steaming (L-ST) and with a pressure cooker (L-PC), contain high RS, ranging between 22.51 and 27.03 g 100 g-1 dry matter, and have potential as prebiotic food as indicated by the increased viability of L. rhamnosus and L. plantarum bacteria grown in media with cooked dried-growol supplements of L-ST or L-PC, with a prebiotic index between 0.82 and 0.90. Thus, dried-growol has the potential to be a functional prebiotic food that can serve as a staple food that is beneficial for health.